Neuroendocrine tumors of the gynecologic tract: A Society of Gynecologic Oncology (SGO) clinical document - Gardner, Ginger J.; Reidy-Lagunes, Diane; Gehrig, Paola A. (Gynecologic oncology, 2011)
Neuroendocrine tumors of the gynecologic tract are rare, and pose a significant clinical challenge because of the tumor heterogeneity and lack of standardized guidelines for treatment. This manuscript summarizes the available literature concerning these tumors in an effort to provide the clinician a framework from which to guide patient management. MEDLINE was searched for all research articles published in English between January 1, 1966 and March 1, 2011 in which the studied population included women diagnosed with neuroendocrine tumors of the gynecologic tract. Although preference was given to prospective studies, studies were not limited by design or by numbers of subjects given the limited availability of reports. Most, but not all, neuroendocrine tumors of the gynecologic tract have an aggressive clinical course and those of the cervix histologically and clinically share similarities with small cell lung cancer. Cumulative data supports a multi-modality therapeutic strategy. A proposed management algorithm for neuroendocrine carcinomas of the cervix is outlined. For less frequent disease sites including the adnexa, uterus, vagina and vulva, as well as well differentiated carcinoid tumors, surgical resection is appropriate in selected cases. Etoposide/platinum based chemotherapy is used for neuroendocrine carcinomas but not for well differentiated carcinoid tumors. Well differentiated carcinoid and atypical carcinoid tumors should be managed similar to gastroenteropancreatic NETs (GEP-NETs). Most neuroendocrine tumors of the gynecologic tract require a multi-modality therapeutic approach, determined by extent of disease and primary organ of involvement. Pathologic diagnosis is critical to guide therapy. ► Etoposide/cisplatin should be considered for early stage cervical SCC. ► Fertility sparing surgery can be considered for ovarian NETs. ► Gynecologic NETs are rare and data is limited.